A rare earth doped nanocomposite material and its preparation method and application
By introducing a bowl-shaped array of nano-precious metals into rare earth up-conversion nanomaterials, local plasma resonance is used to enhance the luminescence of rare earth nanoparticles, the problem of low luminescence efficiency of rare earth nanomaterials is solved, and high stability and efficient fluorescence enhancement is achieved. Suitable for display, imaging and detection fields.
Patent Information
- Application Number
- CN202211626108.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-15
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-12-15
AI Technical Summary
The low luminescence efficiency of rare earth upconverted nanomaterials limits their application in the fields of display, imaging and detection. The material preparation process of existing methods is complex and unstable, making it difficult to be suitable for large-scale applications.
The combined material of nano-precious metal bowl-shaped array and rare earth up-converted nanoparticles is used to enhance the luminescence intensity of rare earth nanoparticles by matching the local plasma resonance absorption peak with the emission peak of rare earth nanoparticles, and nanometers are prepared by co-precipitation method and template method. The precious metal bowl-like array and rare earth up-convert nanoparticles to form stable rare earth-doped nanocomposites.
It significantly improves the luminous intensity of rare earth nanoparticles, improves the stability and uniformity of the material, broadens the detection range, improves the detection effect, and is suitable for large-scale applications.
Smart Images

Figure CN116285989B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nanomaterials, and specifically relates to a rare earth doped nanocomposite material, a preparation method thereof, and an application thereof in molecular detection. Background Art
[0002] Rare earth elements have a rich energy level structure. Specific rare earth ion combinations can undergo upconversion, that is, the process of absorbing low-energy photons and emitting high-energy photons. They can effectively utilize near-infrared light and show great application potential in display, imaging, detection and biological fields.
[0003] However, the rare earth upconversion process is inefficient, resulting in weak luminescence intensity, which seriously limits its application development. Therefore, technical measures must be taken to improve its luminescence intensity. The existing methods to reduce energy loss and enhance upconversion fluorescence mainly include the following three:
[0004] 1. Construct a multi-layer core-shell structure to protect the luminescence center away from quenching factors in the environment;
[0005] 2. Optimize the concentration of doping ions and design a component composition scheme with high doping concentration while avoiding concentration quenching;
[0006] 3. Introducing antenna molecules can improve the light absorption capacity of nanomaterials, thereby improving the upconversion efficiency.
[0007] However, the material preparation process of the above method is complicated and not suitable for large-scale applications. The instability of organic antenna molecules will affect the overall performance of the material. Therefore, it is still necessary to develop a fluorescence enhancement method with strong stability and simple preparation.
[0008] In recent years, nano-precious metal bowl arrays have continued to attract attention due to their unique periodic morphology and good signal enhancement. For example, the patent with publication number CN 110668395 A discloses a method for preparing a highly ordered and axisymmetric nano-periodic structure. The invention uses a nano-bowl structure as the basic structure, and regulates the hot spot distribution of the nano-bowl by incident light, thereby achieving controllable growth position and size of silver nanoparticles, and preparing a nano-ring periodic structure composed of highly ordered, localized growth silver nanoparticles. This method is different from traditional physical methods and chemical corrosion methods. It is a new method for preparing nano-periodic structures, which is expected to be applied to the preparation of more periodic structures.
[0009] In the nano-precious metal bowl-shaped array structure, the precious metal nanostructure can focus the energy of the incident light spatially to the nanoscale range through localized surface plasmon resonance enhancement, and regulate the transmission of light energy at the nanoscale, thereby generating a huge electromagnetic field enhancement, that is, "hot spots". The highly uniform pore structure of the gold and silver nano-bowl-shaped array and the presence of many "hot spots" can greatly increase the luminescence intensity of the nanoparticles at the "hot spots" in the bowl, and this array structure has high stability and uniformity.
[0010] Therefore, it is very necessary to develop a nanomaterial that utilizes a nano-noble metal bowl-shaped array structure to enhance the fluorescence properties of rare earth upconversion nanoparticles. This nanomaterial has good application space in the fields of display, imaging, and detection on a macro scale. Summary of the invention
[0011] In view of the bottleneck problems existing in the current field, the present invention provides a rare earth doped nanocomposite material and its preparation method and application. The rare earth doped nanocomposite material is assembled from a nano noble metal bowl array and rare earth upconversion nanoparticles, and the localized plasma resonance absorption peak of the nano noble metal bowl array matches the emission peak of the corresponding rare earth upconversion nanoparticles; in the hot spot in the nano noble metal bowl, under the irradiation of the excitation light, the luminescence of the rare earth upconversion nanoparticles will be greatly enhanced.
[0012] The present invention adopts the following technical solution:
[0013] A method for preparing a rare earth-doped nanocomposite material comprises the following steps:
[0014] (1) preparing rare earth upconversion nanoparticles;
[0015] (2) Preparation of nano-precious metal bowl-shaped arrays;
[0016] (3) Adding the rare earth upconversion nanoparticles obtained in step (1) to the nano-precious metal bowl-shaped array obtained in step (2) to obtain the rare earth-doped nanocomposite material.
[0017] Preferably, the structural formula of the rare earth upconversion nanoparticles is NaY 0.8-x F4:Yb 0.2 ,Ln x , wherein Ln is selected from one of Er and Tm, and x is 0.02 or 0.005. Further preferably, the rare earth upconversion nanoparticles are NaYF4:Yb,Er or NaYF4:Yb,Tm.
[0018] Preferably, the precious metals include gold and silver.
[0019] Preferably, the diameter of the nano bowl in the nano noble metal bowl array is 200 nm to 5 μm.
[0020] Preferably, the particle size of the rare earth upconversion nanoparticles is between 15 nm and 50 nm.
[0021] Preferably, in step (1), the present invention prepares the rare earth upconversion nanoparticles based on a coprecipitation method. Further preferably, the method for preparing the rare earth upconversion nanoparticles comprises the following steps:
[0022] (1-a) Add oleic acid, 1-octadecene, Y(CH3COO)3, Yb(CH3COO)3, and then add Er(CH3COO)3 or Tm(CH3COO)3 into a container, stir and heat the mixed solution in an oil bath to 130-140°C to remove moisture in the reaction system, then raise the temperature to 145-155°C and keep the temperature for 1h-2h to form rare earth oleate;
[0023] (1-b) After cooling the mixed solution obtained in step (1-a) to 45-55° C., add 2 mL of 0.5 M NaOH methanol solution and 3-4 mL of 0.4 M NH4F methanol solution, which are mixed evenly, and keep the mixture warm for 30-60 min to form crystal nuclei, and then heat the mixture to 110-140° C. to remove methanol and water;
[0024] (1-c) further removing water and air from the mixed solution obtained in step (1-b), connecting nitrogen, raising the temperature to 260-300° C., maintaining for 1-1.5 hours, and performing crystal growth;
[0025] (1-d) After cooling the mixed solution obtained in step (1-c) to room temperature, ethanol is added to precipitate the product, centrifuged, and washed to obtain the rare earth upconversion nanoparticles.
[0026] Preferably, in the preparation of the rare earth up-conversion nanoparticles, in step (1-b), the volume ratio of oleic acid to 1-octadecene is 2:2-3.
[0027] Preferably, in the preparation of the rare earth upconversion nanoparticles, in step (1-b), the molar ratio of Y(CH3COO)3, Yb(CH3COO)3 and Er(CH3COO)3 is 38-40:9-11:1; or, the molar ratio of Y(CH3COO)3, Yb(CH3COO)3 and Tm(CH3COO)3 is 156-162:38-42:1.
[0028] Preferably, in step (2), the method for preparing the nano noble metal bowl-shaped array comprises the following steps:
[0029] (2-a) Spreading polystyrene beads on a clean silicon wafer substrate as a template;
[0030] (2-b) A noble metal film is evaporated on the surface of the polystyrene beads, and then the polystyrene beads are removed to obtain the nano noble metal bowl-shaped array.
[0031] Preferably, in the preparation of the nano noble metal bowl-shaped array, in step (2-b), a silicon wafer loaded with polystyrene beads and a noble metal film is placed in a tetrahydrofuran solution to dissolve and remove the polystyrene beads, washed, and dried to obtain the nano noble metal bowl-shaped array.
[0032] Preferably, step (3) is specifically as follows: placing the nano-precious metal bowl-shaped array obtained in step (2) on a spin coater for vacuum fixation, dripping the colloidal solution of rare earth upconversion nanoparticles obtained in step (1) onto a silicon wafer, turning on the spin coater to allow the nanoparticles to evenly fall into the bowl-shaped array structure, and throwing out excess rare earth upconversion nanoparticles.
[0033] The present invention also provides a rare earth doped nano composite material, which is obtained by adding rare earth up-conversion nano particles to a nano noble metal bowl-shaped array.
[0034] The rare earth-doped nanocomposite material is prepared according to the preparation method provided by the present invention.
[0035] The invention also provides an application of the rare earth doped nanocomposite material in molecular detection.
[0036] The application of the rare earth doped nanocomposite material provided by the present invention in the detection of molecules can be realized in the following ways: 1) direct detection: using the condition that the absorption peak of the molecule to be detected overlaps with the emission peak of the rare earth ion, when the molecule to be detected exists, the emission peak of the rare earth ion will decrease; 2) indirect detection: using a detection agent that can react with the molecule to be detected, the absorption peak of the detection agent has a certain overlap with the emission peak of the rare earth ion, when the detection agent exists, the emission peak of the rare earth ion decreases, and when the molecule to be detected enters the system, the molecule to be detected reacts with the detection agent, so that the absorption peak of the detection agent moves, increases or decreases, thereby causing the emission peak of the rare earth ion to increase or decrease accordingly. The enhancement of the emission peak of the rare earth ion by the noble metal bowl-shaped array can broaden the concentration detection range of the molecule to be detected and improve the detection effect.
[0037] Compared with the prior art, the present invention has at least the following beneficial effects:
[0038] 1. The precious metal and rare earth nanoparticles in the rare earth-doped nanocomposite material prepared by the preparation method provided by the present invention have high physicochemical stability, and the array periodic repeatability prepared by using the template is good. Therefore, the composite material has high stability and good uniformity. In the hot spot in the nano precious metal bowl, under the irradiation of excitation light, the luminescence of the rare earth upconversion nanoparticles will be greatly enhanced.
[0039] 2. The present invention utilizes a nano-noble metal bowl-shaped array structure to enhance the fluorescence performance of rare earth up-conversion nanoparticles. The localized plasma resonance absorption peak of the nano-noble metal bowl-shaped array matches the emission peak of the corresponding rare earth up-conversion nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Schematic diagram of rare earth upconversion nanoparticles - a single nano-precious metal bowl-shaped structure.
[0041] Figure 2 This is a transmission electron microscope photograph of the NaYF4:Yb, Er rare earth upconversion nanoparticles prepared in Example 1.
[0042] Figure 3 These are microscope photos of the NaYF4:Yb,Er rare earth up-conversion nanoparticles loaded onto a silicon wafer and a 500 nm gold bowl array respectively, as measured in Example 1. The dotted circle is the emission light spot of the rare earth up-conversion nanoparticles.
[0043] Figure 4 This is the emission spectrum of NaYF4:Yb,Er rare earth up-conversion nanoparticles measured in Example 1 when they are loaded onto a silicon wafer and a 500nm gold bowl structure array respectively.
[0044] Figure 5 This is a transmission electron microscope photograph of the NaYF4:Yb,Tm rare earth upconversion nanoparticles prepared in Example 2.
[0045] Figure 6 This is the emission spectrum of NaYF4:Yb, Tm rare earth up-conversion nanoparticles measured in Example 2 when they are loaded onto a silicon wafer and a 5μm gold bowl structure array respectively. DETAILED DESCRIPTION
[0046] The present invention will be further described below in conjunction with the accompanying drawings and specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0047] Example 1
[0048] Preparation and optical properties of NaYF4:Yb,Er rare earth upconversion nanoparticles-500nm gold bowl composite material.
[0049] Put a stirrer in a two-necked flask, add 4mL oleic acid and 6mL 1-octadecene, then add 1.56mL Y(CH3COO)3, 0.4mL 0.2M Yb(CH3COO)3 and 0.04mL 0.2M Er(CH3COO)3 aqueous solution respectively, heat the mixed solution to 135℃ in an oil bath to remove moisture in the reaction system, then continue to heat to 150℃ and keep warm for 1h; after cooling to 50℃, add 2mL 0.5M NaOH methanol solution and 4mL 0.4M NH4F methanol solution mixed evenly to the two-necked flask, keep warm for 40min, then slowly heat to 110℃ to remove methanol and moisture. Connect a vacuum pump to further remove moisture and air in the solution for 8min, fill with nitrogen, and then evacuate. Repeat three times and continue to connect nitrogen, quickly heat to 300℃ and keep for 1.5h. After cooling to room temperature, ethanol was added to the reaction solution to precipitate the product, centrifuged for 10 min at 4000 r / min, washed three times with ethanol, and dispersed in 4 mL of cyclohexane for later use.
[0050] Ethanol and polystyrene (PS) colloidal suspension were mixed in a volume ratio of 10000:1, and a layer of polystyrene (PS) beads with a particle size of 500 nm was spread on the cleaned silicon wafer substrate as a template using the gas-liquid interface self-assembly method. -4 Pa, a 250nm thick gold film was evaporated on the surface of a single-layer PS ball template at a certain evaporation speed. After taking it out, the silicon wafer loaded with PS balls and gold film was placed in a tetrahydrofuran solution to dissolve and remove the PS balls, washed with ethanol several times, and finally dried with nitrogen to prepare a nano-gold bowl array structure on the silicon wafer. The obtained silicon wafer was placed on a spin coater and fixed in vacuum, 200μL of a colloidal solution of rare earth upconversion nanoparticles was dripped onto the silicon wafer, the spin coater was turned on at a low speed to evenly drop the nanoparticles into the bowl-shaped array structure, and the excess nanoparticles were thrown out. The resulting composite structure is as shown in FIG. Figure 1 shown.
[0051] Figure 2 This is a transmission electron microscope image of the prepared NaYF4:Yb,Er rare earth upconversion nanoparticles. The particle size is about 23nm and the size distribution is uniform.
[0052] from Figure 3 It can be seen that when the rare earth upconversion nanoparticles are loaded on the 500nm gold bowl array, the luminescent spot is significantly larger than when they are directly loaded on the silicon wafer. Further, the luminescent spectrum of NaYF4:Yb,Er rare earth upconversion nanoparticles is detected, such as Figure 4 As shown, the three characteristic emission peaks correspond to Er 3+ Ionic 2 H 11 / 2 → 4 I 15 / 2 (~521nm), 4 S 3 / 2 → 4 I 15 / 2 (~541nm) and 4 F 9 / 2 → 4 I15 / 2 (~654nm) transition, whether loaded on silicon wafer or gold bowl array, the peak shape is consistent, there is no shift, only the intensity is different, the fluorescence generated by the nanoparticles in the gold bowl array is significantly stronger than that on silicon wafer. After calculation, when in the gold bowl array, the fluorescence of NaYF4:Yb,Er nanoparticles at ~521nm was enhanced by about 7.3 times, the fluorescence at ~541nm was enhanced by about 14 times, and the fluorescence at ~654nm was enhanced by about 16 times, confirming the enhancement effect of 500nm gold bowl array on the fluorescence of rare earth upconversion nanoparticles. The different fluorescence enhancement effects at different wavelengths are due to the different intensities of the localized plasma resonance absorption peak of the gold bowl array at each wavelength, resulting in selective enhancement of fluorescence.
[0053] Example 2
[0054] Preparation and optical properties of NaYF4:Yb,Tm rare earth upconversion nanoparticles-5μm gold bowl composite materials.
[0055] Put a stirrer in a two-necked flask, add 4mL oleic acid and 6mL 1-octadecene, then add 1.59mL Y(CH3COO)3, 0.4mL 0.2M Yb(CH3COO)3 and 0.1mL 2M Tm(CH3COO)3 aqueous solution respectively, heat the mixed solution to 135℃ in an oil bath to remove moisture in the reaction system, then continue to heat to 150℃ and keep warm for 1h; after cooling to 50℃, add 2mL 0.5M NaOH methanol solution and 4mL 0.4M NH4F methanol solution mixed evenly to the two-necked flask, keep warm for 40min, then slowly heat to 110℃ to remove methanol and moisture. Connect a vacuum pump to further remove moisture and air in the solution for 8min, fill with nitrogen, and then evacuate. Repeat three times and continue to connect nitrogen, quickly heat to 300℃ and keep for 1.5h. After cooling to room temperature, ethanol was added to the reaction solution to precipitate the product, centrifuged for 10 min at 4000 r / min, washed three times with ethanol, and dispersed in 4 mL of cyclohexane for later use.
[0056] Using a dispersion of ethanol and polystyrene (PS) colloidal suspension mixed in a volume ratio of 10000:1, a layer of polystyrene (PS) beads with a particle size of 5 μm was spread on a clean silicon wafer substrate using the gas-liquid interface self-assembly method as a template. -4 Pa, a 2.5 μm thick gold film was evaporated on the surface of a single-layer PS ball template at a certain evaporation speed. After taking it out, the silicon wafer loaded with PS balls and gold film was placed in a tetrahydrofuran solution to dissolve and remove the PS balls, washed with ethanol several times, and finally dried with nitrogen to prepare a nano-gold bowl-shaped array structure on the silicon wafer. The obtained silicon wafer was placed on a spin coater and fixed in vacuum, 200 μL of a colloidal solution of rare earth upconversion nanoparticles was dripped onto the silicon wafer, the spin coater was turned on at a low speed to evenly drop the nanoparticles into the bowl-shaped array structure, and the excess nanoparticles were thrown out. The resulting composite structure is as shown in FIG. Figure 1 shown.
[0057] Figure 5 This is a transmission electron microscope image of the prepared NaYF4:Yb,Tm rare earth upconversion nanoparticles. The particle size is about 31nm and the size distribution is uniform.
[0058] The luminescence spectrum of NaYF4:Yb,Tm rare earth upconversion nanoparticles was detected, such as Figure 6 As shown, the three characteristic emission peaks correspond to Tm 3+ Ionic 1 G4→ 3 H6 (~473nm), 1 G4→ 3 F4 (~646nm) and 3 H4→ 3 H6 (~802nm) transition, whether loaded on silicon wafer or gold bowl array, the peak shape remains consistent, no shift occurs, only the intensity is different, the fluorescence generated by the nanoparticles in the gold bowl array is significantly stronger than that generated on silicon wafer. After calculation, when in the gold bowl array, the fluorescence of NaYF4:Yb,Tm nanoparticles at ~473nm has been enhanced by about 38 times, the fluorescence at ~646nm has been enhanced by about 27 times, and the fluorescence at ~802nm has been enhanced by about 29 times, confirming the enhancement effect of 5μm gold bowl array on the fluorescence of rare earth upconversion nanoparticles.
[0059] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing a rare earth-doped nanocomposite material, characterized in that: The following steps are involved: (1) Preparation of rare earth upconversion nanoparticles; (2) Preparation of nano-precious metal bowl-shaped arrays; (3) adding the rare earth upconversion nanoparticles obtained in step (1) to the nano noble metal bowl-shaped array obtained in step (2) to obtain the rare earth doped nanocomposite material, In step (2), the method for preparing the nano noble metal bowl-shaped array comprises the following steps: (2-a) Spread polystyrene beads on a clean silicon wafer substrate as a template; (2-b) A noble metal film is evaporated on the surface of the polystyrene beads, and then the polystyrene beads are removed to obtain the nano noble metal bowl-shaped array.
2. The preparation method according to claim 1, characterized in that: The diameter of the nano bowl in the nano noble metal bowl-shaped array is 200 nm~5 μm.
3. The preparation method according to claim 1, characterized in that: The particle size of the rare earth upconversion nanoparticles is 15 nm to 50 nm.
4. The preparation method according to claim 1, characterized in that: In step (1), the method for preparing rare earth upconversion nanoparticles comprises the following steps: (1-a) Add oleic acid, 1-octadecene, Y(CH3COO)3, Yb(CH3COO)3, and then Er(CH3COO)3 or Tm(CH3COO)3 into a container, stir and heat the mixed solution in an oil bath to 130-140°C to remove water from the reaction system, then raise the temperature to 145-155°C and keep it for 1 h-2 h to form rare earth oleate; (1-b) After cooling the mixed solution obtained in step (1-a) to 45-55°C, add 2 mL of 0.5 M NaOH methanol solution and 3-4 mL of 0.4 M NH4F methanol solution, which are evenly mixed, and keep warm for 30-60 min to form crystal nuclei, and then raise the temperature to 110-140°C to remove methanol and water; (1-c) further removing water and air from the mixed solution obtained in step (1-b), connecting nitrogen, raising the temperature to 260-300° C., maintaining for 1-1.5 h, and performing crystal growth; (1-d) After the mixed solution obtained in step (1-c) is cooled to room temperature, ethanol is added to precipitate the product, centrifuged, and washed to obtain the rare earth upconversion nanoparticles.
5. The preparation method according to claim 4, characterized in that: In step (1-b): The molar ratio of Y(CH3COO)3, Yb(CH3COO)3 and Er(CH3COO)3 is 38-40:9-11:1; Or, the molar ratio of Y(CH3COO)3, Yb(CH3COO)3 and Tm(CH3COO)3 is 156~162:38~42:
1.
6. The preparation method according to claim 1, characterized in that: Step (3) is specifically as follows: placing the nano-precious metal bowl-shaped array obtained in step (2) on a spin coater for vacuum fixation, dripping the colloidal solution of rare earth upconversion nanoparticles obtained in step (1) onto a silicon wafer, turning on the spin coater to allow the nanoparticles to evenly fall into the bowl-shaped array structure, and throwing out excess rare earth upconversion nanoparticles.
7. A rare earth doped nanocomposite material, characterized in that: The rare earth-doped nanocomposite material is prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation method of highly ordered and axisymmetric nano periodic structure
CN110668395A
Gold nanorod vertical array / up-conversion material nanometer composite film for modulating solar spectrum and preparation method of gold nanorod vertical array / up-conversion material nanometer composite film
CN111848997A
